Association of CACNG6 polymorphisms with aspirin-intolerance asthmatics in a Korean population - Jang An-Soo; Park Jong-Sook; Uh Soo-Taek; Cheong Hyun; Park Byung-Lae; Pasaje Charisse; Park Tae; Kim Jason; Bae Joon; Kim Jeong-Hyun; Lee Jin; Kim Mi-Kyeong; et al. (BMC, 2010)
Abstract Background Aspirin-intolerant asthma (AIA) occurs in the lower and upper airways through excessive production of leukotrienes upon administration of non-steroidal anti-inflammatory drugs (NSAIDs). One of the three symptoms of AIA is nasal polyposis, a chronic inflammatory disease that is related to the function of calcium ion in recruitment of immune cells during airway inflammation. It has been implicated that bronchodilation in the airway is related to Ca(2+) regulation. The calcium channel, voltage-dependent, gamma subunit 6 (CACNG6) gene encodes a protein that stabilizes the calcium channel. Methods To study the associations between AIA and polymorphisms in CACNG6 gene, eight variants were genotyped in 102 AIA cases and 429 aspirin-tolerant asthma (ATA) controls. Logistic analyses were used to evaluate the associations of CACNG6 polymorphisms with AIA. Results Statistical analyses revealed that a single nucleotide polymorphism (SNP; rs192808C > T; P = 0.0004, Pcorr = 0.0029, OR = 2.88 in co-dominant model; P = 0.0005, Pcorr = 0.0036, OR = 2.99 in dominant model) in intron and a haplotype unique to this variant (CACNG6_BL1_ht6; P = 0.003, Pcorr = 0.02, OR = 2.57 in co-dominant model, P = 0.001, Pcorr = 0.0087, OR = 2.81 in dominant model) were significantly associated with the risk of AIA. Conclusions Our results suggest that the CACNG6 variants might be associated with the risk of AIA in a Korean population.